The Impact of Baptist Christianity on the Lost MORUNG (the house of wisdom) in the Context of the Konyak - , LEMWANG W CHUHWANGLIM, Prof. Dr. Mark Woodward ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The purpose of this study is to critically analyse the turning point or conjunction between the Konyak culture and Baptist Christianity when missionaries came to Konyak land. To help people to find out the impact of Baptist Christianity toward the mass conversion of the Konyaks rapidly and the disappearance of most significant culture of Morung. To find a way out to strengthen the Konyak cultural practices mostly the Morung which has become today a fear of disappearing and other cultural practices in addition. The concept of animism among the Konyaks has been understood in terms of the spirits worship. Drawing this line, many fore-parents cultural practices were put into the box of the spirits worship and the Morung cultural practice which is the focus of the thesis was considered a place of spirits worship and against the Baptist Christianity, after the Konyaks accepted the Baptist Christianity since 1950. Interview the sampled (18 older people above 50 years and 16 young people between 20-40 years) people from the Mon District is the prior method applied in this research. Other resources like literature review and personal experienced are also included. The research finding from the sample people have vividly contributed toward identifying the cause of the Baptist Christianity approach to the Morung cultural practices as against the Baptist Christianity among the Konyaks. Out of 30-40 sample people, 90 % have mentioned that headhunting was the core issue for the Church to propagate the Gospel against the Morung cultural practices and the remaining people indicated both toward the modernization and development.